Comparison of Stain Effects of Nicotine and Beverages on Different Cad-Cam Materials - Mehmet Ali Kılıçarslan; Burak Gökdeniz; Gülbike Demirel; Ahmet Kürşad Çulhaoğlu (Ankara University, 2022)
Purpose: This study aimed to compare the effect of smoking cigarettes and drinking beverages and also polishing procedures on the discoloration of CAD/CAM materials. Materials and Methods: Resin nanoceramic (Lava Ultimate-RN), feldspar ceramic (CEREC Blocs Ceramics-FC) and lithium disilicate glass-ceramic (IPS e.max® CAD-LDC) specimens (5X5 X2 mm) were used for this study. Initially, baseline surface roughness (Ra) and color values (L*, a*, b*) of the specimens were measured with profilometer and chroma meter. Then the specimens were exposure nicotine, coffee and red wine. The first discoloration values of each specimen were measured. Then, all of the specimens were subjected to re-polishing procedures. Than, the surface roughness and color values of each specimen were measured. The specimens were subjected to the same staining process again. After exposure of the specimens to the staining agents, the second staining value was measured. Two-way analysis of variance (ANOVA) was used for normally distributed groups, and the Kruskal-Wallis test was used for non-normally distributed groups. Results: Statistically significant ΔE* values were observed for RN (8.26±1.55) and FC (7.69±1.52) for nicotine in the first staining group. The maximum total color changes were observed in the nicotine group for all of the material specimens. Nicotine caused the highest color changes on the test materials than coffee and wine. Surface roughness did not show a statistically significant difference based on the staining agents for any of the materials within a group (p lt;0.05). Conclusions: It was observed that nicotine staining is far stronger than beverage staining.